Perkembangan Nilai Tukar Petani (NTP) Jawa Barat dan Korelasinya dengan Tenaga Kerja, Inflasi, dan Produk Domestik Regional Bruto (PDRB) Sektor Pertanian Jawa Barat - Juri Juswadi; Pandu Sumarna (Lembaga Penelitian dan Pengabdian Universitas Winaya Mukti, 2024)
This research aims to identify the developments of Farmer Exchange Rate (FER) in the West Java Agricultural Sector in the period 2000-2022. This paper analyzes the extent of the correlation between Agricultural Sector Labor, the Inflation Rate variables, and the Gross Regional Domestic Product (GRDP) of Agricultural Sector on the FER in the in West Java. The correlation identification between these variables was analyzed through Pearson’s Product Moment Correlation analysis based on West Java FER. The FER data is obtained from the Farmer Exchange Rate Statistics published by the Central Statistics Agency (BPS). The research results show: a) There are variations in the FER value during the period 2005-2022 with an average of 103.99; b) The West Java Agricultural Sector Labor variable has a moderate positive linear correlation with West Java's FER; c) The West Java Agricultural Sector variable GRDP has weak negative linear correlation with West Java's FER; and d) The West Java inflation variable has a weak positive linear correlation with West Java's FER.